Germinação de sementes e respostas fotossintéticas de Miconia albicans (Sw.) Triana (Melastomataceae) e sua capacidade de estabelecimento em veredas alteradas - Rezende, Arthur Ferreira (2021)
The Cerrado is composed of a mosaic of phytophysiognomies, has different environments, with wetlands contrasting with areas under water-restricted conditions. Between an area and other species that get priority in two environments. The genus Miconia, with great representation at the Panga Ecological Station in Uberlândia - MG, is present both in the cerrado stricto sense and on the edge of the palm swamp. Miconia albicans, a species that occurs widely in the cerrado, found on the edge of the palm swamp of the Panga Ecological Station, which is drying due to disturbances in the surroundings of the conservation unit. This study aims to find differences in intraspecific variability and germination of Miconia albicans seeds, as well as to evaluate the gas exchange of the species in both environments. In the first chapter, the germination processes were affected by the intraspecific variability imposed by the palm swamp mother plants in the expression of germinability, average germination time and average speed. In the second chapter, the species showed greater efficiency in its gas exchange on the palm swamp for transpiration rate, intercellular concentration of CO2 and instantaneous efficiency in water use. With this, we were able to infer that M. albicans can be considered a biological model and bioindicator of disturbed palm swamp, acting as a potential dominant species.